The Importance of Magnetic Reflection Condition and Polarization Factor: Case Study of MnF2 - A. Purwanto (Atom Indonesia, 2010)
Neutron diffraction has been widely accepted as a versatile tool to investigate magnetic structure of crystalline materials, which contribute significantly to the scientific and technological advances. Starting from a general formulation of the magnetic structure factor, one can often simplify the formulation depending on the crystallographic structure and the magnetic wave propagation vector of the sample. The simplification allows magnetic moment coupling and polarization deduction without the need of the refinement process. This paper elaborates such simplification for MnF2 to provide the determination of the magnetic moment coupling and polarization direction simply based on the reflection condition and polarization factor. The determination of the magnetic structure excluding its magnitude by the reflection condition and polarization factor is much more conclusive than by any magnetic structure refinement. Furthermore, MnF2 illustrates a rare compound that has antiferromagnetic structure with zero magnetic wave propagation vector, i.e.; it has the same antiferromagnetic and crystallographic unit cell.Received:19 May 2009; Received: 30 August 2010; Accepted: 31 August 2010